Age Estimation from Sternum for Age Group 25 Years Onwards - Chopra, Mukul; Singh, Harpreet; Kohli, Kanika; Aggarwal , O P (Journal of Indian Academy of Forensic Medicine, 2015)
Age is one of the important parameters for the Identification of an individual whether the individual is alive, dead or human remains. A criminal will tell his age wrong to the investigating agencies to get less punishment from the court. Various government agencies are giving benefits like employment, pension and medical reimbursement according to age of a person. The age plays a vital role in sports competition. A person who’s age more than 60 years is a senior citizen. The railways authority gives concession of 40% to male senior citizens and 50% to female senior citizens. The benefits are also on the income tax. Age is also important in onset of various diseases. The sternum can be visualized by radiography for age estimation. The earliest age of fusion of the Xiphisternum with the body of the sternum was 26 years in the males and 26 years in the females also. The earliest age of fusion of the manubrium with the body of the sternum was 29 years in males and 35 years in the females